Manajemen Prestasi Santri Anwaha : Penelitian - Syahrani; Maulana Sasty; Muhammad Ikhsan; Muhammad Ilham Fikri; Fatimatul Aulia; Hayatun Nufuz (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the management of student achievement in improving the quality of learning in Islamic boarding schools. This research uses the literature review method by analyzing various academic sources related to learning achievement management. The results showed that santri learning achievement is influenced by various factors, such as learning discipline, the role of homeroom teachers, activeness in learning, and involvement in extracurricular activities. Data obtained from MTs Anwarul Hasaniyyah Tabalong shows that the level of attention, activeness, and discipline of santri in learning is still relatively low, although there is an increase in enthusiasm for learning after participating in extracurricular activities. Student achievement management includes planning, monitoring, evaluating, and developing academic and non-academic in order to achieve optimal learning outcomes. With the implementation of more effective strategies, such as increasing study discipline and involvement in additional activities, santri achievement can continue to be improved.